Diseño de un centro educativo – terapéutico para niños con discapacidad intelectual en Guayaquil - Flores Castillo, Nicole Tahis (2024)
This proposal aims to develop the architectural design of a therapeutic educational center for children with intellectual disabilities, especially ASD (autism spectrum disorder) through phenomenology, located north in the city of Guayaquil, specifically the Cdla. Garzota. The project seeks to solve the lack of this type of establishments that support the development of children who suffer from this disease. The initiative is presented as an innovative and necessary solution to improve the quality of life and development of children with ASD in Guayaquil. By integrating disability, education and therapy into the architectural design, the Therapeutic Educational Center seeks not only to offer an appropriate educational environment, but also to promote the inclusion and active participation of these children in society. This project represents an important step towards creating a more inclusive and accessible environment for people with disabilities in the city.